Handbook of food processing equipment - Saravacos, George (Food engineering series, 2016)
Contents: design of food processes and food processing plants; design and selection of food processing equipment; mechanical transport and storage equipment; mechanical processing equipment; mechanical separation equipment; heat transfer equipment;...